Detection of Abnormal Spontaneous Brain Activity Patterns in Patients With Orbital Fractures Using Fractional Amplitude of Low Frequency Fluctuation - Kang, Min; Gao, YuXuan; Zhang, LiJuan; Liang, RongBin; Li, QiuYu; Shu, HuiYe; Pan, YiCong; Ying, Ping; Xu, SanHua; Yi, Shao (Frontiers in Neurology, 2022)
Abstract Background: To date, no in-depth study has been conducted on the intrinsic pathological relationship between altered brain activity and related behavioral changes in patients with orbital fracture (OF). Purpose: The present research aimed to explore the potential functional network cerebrum activities in patients with OF using resting state functional magnetic resonance imaging–fractional amplitude of low-frequency fluctuation (rsfMRI-fALFF). This technique can reveal dynamic functional changes in specific cerebrum areas. Methods: Twenty patients with OF and 20 healthy controls (HCs) were included, closely matched in terms of gender, age, weight and education level. To record spontaneous cerebral activity changes, the rsfMRI-fALFF tool was applied. Receiver operating characteristic (ROC) curves and Pearson’s correlation analysis were used to analyze mean fALFF values in specific cerebrum regions and to explore changes of behavioral changes in OF patients. The Hospital Depression and Anxiety scale was applied to reveal the relationship between emotional states and fALFF values of the right superior temporal gyrus in OF patients. Results: In comparison with HCs, significantly lower fALFF values were detected in the left anterior cingulate gyrus (LACG) and right superior temporal gyrus (RSTG) in patients with OF. ROC curve analysis showed excellent accuracy. The mean fALFF values of the RSTG negatively correlated with the depression score as well as anxiety score. Conclusion: The finding of abnormal spontaneous activities in cerebral regions may contribute to more comprehensive understanding of the potential neural network changes in patients with OF. The changes of fALFF value in patients with OF may help to gauge their emotional changes and clinical recovery level.